Dietary fiber content in clinical ketogenic diets modifies the gut microbiome and seizure resistance in mice - Ezgi Özcan; Kristie B. Yu; Lyna Dinh; Gregory R. Lum; Katie Lau; Jessie Hsu; Mariana Arino; Jorge Paramo; Arlene Lopez-Romero; Elaine Y. Hsiao (Nature Communications)
Abstract The gut microbiome modulates the anti-seizure effects of the ketogenic diet, but how specific dietary formulations differentially modify the gut microbiome in ways that impact seizure outcome is poorly understood. We find that medical ketogenic infant formulas vary in macronutrient ratio, fat source, and fiber content and differentially promote resistance to 6-Hz seizures in mice. Dietary fiber, rather than fat ratio or source, drives substantial metagenomic shifts in a model human infant microbial community. Addition of fiber to a fiber-deficient ketogenic formula restores seizure resistance, and supplementing protective formulas with excess fiber potentiates seizure resistance. By screening 13 fiber sources and types, we identify metagenomic responses in the model community that correspond with increased seizure resistance. Supplementing with seizure-protective fibers enriches microbial genes related to queuosine biosynthesis and preQ0 biosynthesis and decreases genes related to sucrose degradation and TCA cycle, which are also seen in seizure-protected mice that are fed fiber-containing ketogenic formulas. This study reveals that different formulations of ketogenic diets, and dietary fiber content in particular, differentially impact seizure outcome in mice, likely by modifying the gut microbiome. Understanding interactions between diet, microbiome, and host susceptibility to seizures could inform novel microbiome-guided approaches to treat refractory epilepsy.